Comparative Study of the Lipid Lowering Effect of Leaf Extract of Catharanthus roseus & Atorvastatin (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Leaf extract of Catharanthus roseus has medicinal effect.Objective: The purpose of the present study was to compare the effect of leaf extract of Catharanthus roseus (Nayantara) with atorvastatin on serum lipid profile in fat-fed rats.Methodology: This was an experimental animal study carried out in the Department of Pharmacology and Therapeutics at Dhaka Medical College, Dhaka from July 2005 to June 2006 for a period of one year. Adult Long Evans rats of both sexes were used for the study. The rats were divided into seven groups designed as A, B, C, D, E, F and G. Each group was comprised of 8 rats which were treated for 10 days and were sacrificed on 11th day. The experiment were designed to demonstrate the effect of C. roseus on serum lipid profile in hyperlipidaemic rats and the hypolipidaemic effects were compared to a standard oral lipid lowering drug, atorvastatin.Result: A total number of 56 adult Long Evans rats of both sexes were used for the study. Here the effect of leaf extract of C. roseus at different doses on lipid level of fat-fed rats was observed which were compared with the hyperlipidaemic control group. In the same time the effect of Atorvastatin on serum lipid level were observed. The observed lipid lowering effect of leaf extract of C. roseus was evaluated biochemically by significant (p